Analisis Energi dan Eksergi Pembangkit Listrik Tenaga Panas Bumi Dieng dengan Penambahan Sistem Double-Flash Menggunakan Metode Termodinamika - Arya Pramudya Pramundana; Nugroho Agung Pambudi (Nozel : Jurnal Pendididikan Teknik Mesin, 2026)
Indonesia possesses significant geothermal energy potential, accounting for approximately 40% of the world's total reserves. However, its utilization in power generation is still constrained by system efficiency limitations. This study aims to assess the thermal performance of the Dieng Unit 1 Geothermal Power Plant (GPP), which currently operates with a 55 MW single-flash system, and evaluate performance improvements through the integration of a double-flash configuration. A numerical simulation was conducted using the Engineering Equation Solver (EES) software, based on actual operational data from January to February 2025. The results indicate that the implementation of the double-flash system enhances energy efficiency from 71.87% to 84.1%, and exergy efficiency from 43.17% to 49.11%. Net power output increased by 7,560 kW by re-utilizing brine from the high-pressure separator. The study further investigates the effects of pressure variation in the Low Pressure Separator (LPS) and turbine efficiency on power output, identifying 1.6 bar as the optimal pressure for maximizing exergy input. These findings confirm that the double-flash system effectively reduces energy losses and significantly improves the plant’s thermodynamic performance. This research provides valuable insights for optimizing geothermal power systems, offering strategic solutions for sustainable energy development in high-potential regions like Indonesia.